The influence of methods of adding flaxseed flour on the quality indicators of rye bread - A. V. Fedorov; A. A. Khlopov; E. S. Lybenko (Новые технологии)
Modern Russians do not receive enough polyunsaturated fatty acids in their diet, as well as more than half the recommended dietary fiber intake. One of the sources of enriching the human diet with these nutrients can be flaxseed flour. The reason for the rare use of flaxseed flour in baking is the change in the taste and aroma of the finished product. Research to determine the method of adding flaxseed flour was carried out in the laboratory of baking and confectionery production of Vyatka State Technical University. Flax flour was added to bread in the form of sourdough mixed with rye flour, dough from flax flour, and dough from a mixture of flax and rye flour, as well as in dry form into the dough. Organoleptic and physico-chemical quality indicators of semi-finished and finished products were studied. Generally accepted research methods were used in the research. As a result, it has been found that flaxseed flour changes the taste and smell of rye bread to the least extent when it is fermented with yeast in a dough. Fermenting flaxseed flour together with rye flour does not result in the loss of flaxseed taste and aroma. It has been proved that preparing dough using flaxseed flour requires more water than preparing sourdough and dough from rye flour. Sourdough with the addition of flaxseed flour gains acidity faster. Bread with the addition of flaxseed flour in the form of dough is practically no different from the control variant. The crumb of such bread has an acidity of 9.0 degrees, moisture content of 49.9% and porosity of 49%. The tasting has shown that bread with the addition of flax dough among the studied samples scored the highest number of points and was as close as possible to the control version.